ChemInform Abstract: Fast Ion Conducting Nanocrystalline Alkaline Earth Fluorides Simply Prepared by Mixing or Manual Shaking. Issue 30 (4th July 2013) - Scholz, Gudrun; Meyer, Klas; Duevel, Andre; Heitjans, Paul; Kemnitz, Erhard
Abstract Nanocrystalline phase‐pure metal fluorides MF2 (M: Ca, Sr, Ba) are obtained by simple mixing or shaking of alkaline earth hydroxides with NH4F.